2012
DOI: 10.7860/jcdr/2012/4829.2648
|View full text |Cite
|
Sign up to set email alerts
|

Footdrop in the Farmers in Punjab: A Retrospective Electrodiagnostic Study

Abstract: The patients presented with a unilateral footdrop which was due to peroneal palsy, but a decreased peroneal nerve conduction was observed on the contralateral side as well. Thus, it suggested the involvement of the common peroneal nerve bilaterally. The position of sitting during harvesting or weeding was also important in inducing footdrop along with the type of the hand activity, because of occurrence of the footdrop on the side of the dominant hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…One key antecedent to employee turnover is stress Huang et al, 2018), a critical issue that all organizations have to deal with. Job stress occurs when there is an imbalance between job requirements and a worker's ability to cope (Sewwandi & Perera, 2016), a mismatch between employees' capabilities and job demands (Garg, 2010) or an incident or an expected incident within the workplace which is likely to be a threat to employees (Rangrez et al, 2022). The literature shows that, occupational stress influences employees' job satisfaction and organisational commitment, all are major antecedents to employee turnover (Mosadeghrad, 2013).…”
Section: Mediator: Job Stressmentioning
confidence: 99%
“…One key antecedent to employee turnover is stress Huang et al, 2018), a critical issue that all organizations have to deal with. Job stress occurs when there is an imbalance between job requirements and a worker's ability to cope (Sewwandi & Perera, 2016), a mismatch between employees' capabilities and job demands (Garg, 2010) or an incident or an expected incident within the workplace which is likely to be a threat to employees (Rangrez et al, 2022). The literature shows that, occupational stress influences employees' job satisfaction and organisational commitment, all are major antecedents to employee turnover (Mosadeghrad, 2013).…”
Section: Mediator: Job Stressmentioning
confidence: 99%
“…In orthopedic surgery, the microstructure of the implant surface is a crucial factor determining the long-term stability of osseointegrated implants. Currently, the usage of implant with a rough surface has been proved to be effective for improving the stable integration between the surgically placed implants and bone tissue. Compared to a smooth surface, the implants with microroughness structure can provide more space for cell adhesion and increase the bone anchorage, thereby reinforcing the biomechanical interlocking between bone and implants. , The implants with different microroughness levels on their surfaces have been applied in clinical treatment and preclinical studies. Some reports suggested that a surface with higher roughness ensured a higher surface area and in this way a relatively larger bone to implant contact area, which enhanced osteoconductivity and osteogenesis, and thereby improved osseointegration .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the usage of implant with a rough surface has been proved to be effective for improving the stable integration between the surgically placed implants and bone tissue. 1 3 Compared to a smooth surface, the implants with microroughness structure can provide more space for cell adhesion and increase the bone anchorage, thereby reinforcing the biomechanical interlocking between bone and implants. 4 , 5 The implants with different microroughness levels on their surfaces have been applied in clinical treatment and preclinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…whether at fibular head or distal to the fibular neck can be ruled out [7]. Only a few studies are available to know the cause of footdrop in farmers by electrodiagnostic methods [10,11].…”
Section: Introductionmentioning
confidence: 99%